5D CNS+ Software for Automatically Imaging Axial, Sagittal, and Coronal Planes of Normal and Abnormal Second‐Trimester Fetal Brains. (1st October 2016) - Rizzo, Giuseppe; Capponi, Alessandra; Persico, Nicola; Ghi, Tullio; Nazzaro, Giovanni; Boito, Simona; Pietrolucci, Maria Elena; Arduini, Domenico
Abstract : The purpose of this study was to test new 5D CNS+ software (Samsung Medison Co, Ltd, Seoul, Korea), which is designed to image axial, sagittal, and coronal planes of the fetal brain from volumes obtained by 3‐dimensional sonography. The study consisted of 2 different steps. First in a prospective study, 3‐dimensional fetal brain volumes were acquired in 183 normal consecutive singleton pregnancies undergoing routine sonographic examinations at 18 to 24 weeks' gestation. The 5D CNS+ software was applied, and the percentage of adequate visualization of brain diagnostic planes was evaluated by 2 independent observers. In the second step, the software was also tested in 22 fetuses with cerebral anomalies. In 180 of 183 fetuses (98.4%), 5D CNS+ successfully reconstructed all of the diagnostic planes. Using the software on healthy fetuses, the observers acknowledged the presence of diagnostic images with visualization rates ranging from 97.7% to 99.4% for axial planes, 94.4% to 97.7% for sagittal planes, and 92.2% to 97.2% for coronal planes. The Cohen κ coefficient was analyzed to evaluate the agreement rates between the observers and resulted in values of 0.96 or greater for axial planes, 0.90 or greater for sagittal planes, and 0.89 or greater for coronal planes. All 22 fetuses with brain anomalies were identified among a series that also included healthy fetuses, and in 21 of the 22 cases, a correct diagnosis was made. 5D CNS+ was efficient in successfully imaging standard axial, sagittal, and coronal planes of the fetal brain. This approach may simplify the examination of the fetal central nervous system and reduce operator dependency.